Shear Bond Strength to Calcium Hydroxide: Does Cavity Conditioning Make a Difference for Glass Ionomer Based Materials? - Ceren Değer; Leyla Fazlıoglu; Zümrüt Ceren Özduman; Burcu Oglakci Ozkoc; Evrim Eligüzeloğlu Dalkılıç (Clinical Dentistry and Research, 2026)
Background and Aim: Calcium hydroxide liners are commonlyused in deep cavities and their mechanical properties may affect theadhesion of restorative materials. This study evaluated the effect ofcavity conditioner application on the shear bond strength of glassionomer–based materials to a calcium hydroxide liner.Materials and Methods: Sixty acrylic blocks containing standardizedcylindrical cavities were prepared and filled with a calcium hydroxideliner (Dycal, Dentsply Caulk). The specimens were first dividedaccording to cavity conditioner application (with or without 20%polyacrylic acid) and then subdivided based on the restorative materialapplied over the liner: a conventional glass ionomer cement (Fuji IX GPCapsule, GC Dental), a resin-modified glass ionomer cement (Fuji II LCCapsule, GC Dental), or a bioactive ionic resin liner (Activa BioActiveLiner, Pulpdent) (n=10). Shear bond strength testing and failure modeanalysis were performed. Data were analyzed using two-way analysisof variance and Bonferroni post hoc tests (α=0.05).Results: Glass ionomer–based material type significantly affectedshear bond strength (p0.05). Fuji II LC showed the highestbond strength values (6.48±2.67 and 6.81±3.50 MPa), whereasFuji IX GP showed the lowest (3.54±1.98 and 4.13±1.46 MPa).Activa BioActive Liner showed comparable values (4.99±1.84 and6.39±2.34 MPa). Adhesive failures predominated in Fuji IX GP groups,whereas cohesive and mixed failures were more frequent in resin-containinggroups.Conclusion: Cavity conditioner application did not significantlyimprove bond strength to calcium hydroxide. Resin-modified glassionomer may provide more favorable interfacial performance thanconventional GIC, whereas the bioactive ionic resin liner demonstratedcomparable performance to both materials.